Immunoglobulin M in Health and Diseases: How Far Have We Come and What Next? - Jones, Katelyn; Savulescu, Anca F.; Brombacher, Frank; Hadebe, Sabelo (Frontiers in Immunology, 2020)
B lymphocytes are important in secreting antibodies that protect against invading pathogens such as viruses, bacteria, parasites, and also in mediating pathogenesis of allergic diseases and autoimmunity. B lymphocytes develop in the bone marrow and contain heavy and light chains, which upon ligation form an immunoglobulin M (IgM) B cell receptor (BCR) expressed on the surface of naïve immature B cells. Naïve B cells expressing either IgM or IgD isotypes are thought to play interchangeable functions in antibody responses to T cell-dependent and T cell-independent antigens. IgM short-lived plasma cells (SLPCs) and antigen-specific IgM memory B cells (MBCs-M) are critical in the first few days of infection, as well as long-term memory induced by vaccination, respectively. At mucosal surfaces, IgM is thought to play a critical part in promoting mucosal tolerance and shaping microbiota together with IgA. In this review, we explore how IgM structure and BCR signaling shapes B cell development, self and non-self-antigen-specific antibody responses, responses to infectious (such as viruses, parasites and fungal) and non-communicable diseases (such as autoimmunity and allergic asthma). We also explore how metabolism could influence other B cell functions such as mucosal tolerance and class switching. Finally, we discuss some of the outstanding critical research questions in both experimental and clinical settings targeting IgM.